2022
DOI: 10.1039/d2nh00355d
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale dents on cellulose nanofibers: the origin of diverse defects in sustainable fibrillar materials

Abstract: Atomic-scale dent structures on the surfaces of cellulose nanofibers were detected by comparing the experimentally measured and computer-simulated widths of single nanofibers. These dent parts constituted at least 30–40% of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, imperfections, kinks, and dents are also explorable with AFM. In ref , authors reported atomic scale dent defects on CNF as observed with AFM. These deep dents were observed mostly around kinked regions and their extent decreased when CNFs became shorter.…”
Section: Application Of Afm On Cncmentioning
confidence: 98%
“…Moreover, imperfections, kinks, and dents are also explorable with AFM. In ref , authors reported atomic scale dent defects on CNF as observed with AFM. These deep dents were observed mostly around kinked regions and their extent decreased when CNFs became shorter.…”
Section: Application Of Afm On Cncmentioning
confidence: 98%